The Influences of Parenting Patterns, Play Environment, and Family Characteristics on Preschool Children’s Emotions - Lolowang, Roosye Marie; Lumi, Sjerly; Kalesaran, Ferdinand (Universitas Jambi, Indonesia, 2024)
This quantitative study explores the influence of parenting patterns and play environment on preschool children's emotional development, with family characteristics as a moderating factor. The study utilized a path analysis design with structured questionnaires distributed to parents of preschool children in Manado, Tomohon, and Kotamobagu. Data from 90 respondents were analyzed using SmartPLS 4.0 software, measuring variables through Likert-scale responses. The findings demonstrate that parenting patterns and play environments significantly influence children's emotional development, with family characteristics moderating these relationships. The model achieved a high predictive relevance (R² = 0.842; Q² = 0.676), confirming its robust explanatory power. These findings highlight the importance of supportive parenting and enriching play environments, alongside family stability, in fostering healthy emotional development in young children.